The Effect of Implementing the Stem Education Integrated Argumentation (6E+A) to Enhance the Stem Habits of Mind - Karunram, Anongnat; Meesawat, Nataporn; Chuaytanee, Nipaporn; Kongchantree, Phakawan (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2024)
This objective of this research aimed to study the effects of implementing STEM education integrated argumentation (6E+A) to enhance the STEM habits of mind among twelfth-grade secondary school students. The sample group consisted of 113 students from the twelfth grade in the first semester of the academic year 2023 at Mueangtalungpittayasan School. The research tools were including: 1) Three STEM Education integrated argumentation (6E+A) lesson plans, 2) the STEM habits of mind evaluation form and 3) Student interview questionnaire. Statistical used for data analysis included mean, standard deviation, variance analysis, and content analysis. The study found that STEM habits of mind in student were enhanced when implementing STEM education integrated argumentation (6E+A). Furthermore, the analysis of learning activity interpretations and student interviews with a sample group of 5 students using content analysis revealed the presence of all 6 characteristics of STEM habits of mind. These characteristics were ranked in 5 descending order of frequency as follows: Curiosity, Careful Making decision and Recognizing cause and effect were equal, Integrative thinking, Innovative ability and Communicative ability.